The effects of strength and conditioning interventions on serve speed in tennis players: a systematic review and meta-analysis - Deng, Nuannuan; Soh, Kim Geok; Xu, Fan; Yang, Xinggang (Frontiers in Physiology, 2025)
BackgroundTennis performance is highly influenced by serve speed. This review aimed to evaluate and quantitatively compare the efficacy of popular strength and conditioning (S&C) training methods in enhancing the speed of the ball in the serves of tennis players.MethodsFollowing PRISMA guidelines, a systematic search was conducted in the Scopus, Web of Science, SportsDiscuss, and PubMed databases without date constraints, up to July 2024. Studies included in this meta-analysis met PICOS criteria: a) randomized controlled trials with healthy tennis players, b) isolated or combined S&C training programs, c) evaluation of tennis serve speed, and d) adequate data to compute effect sizes (ESs). The PEDro scale was used to assess methodological quality.ResultsOut of 271 identified papers, 16 studies of moderate to high quality were included in the meta-analysis. Resistance training demonstrated a small but significant effect on serve speed (ES = 0.53; p < 0.001), while multimodal training exhibited a moderate and significant effect (ES = 0.79; p = 0.001). However, core training did not have a significant effect on serve speed (ES = 0.32, p = 0.231).ConclusionThe findings suggested that S&C interventions, including resistance and multimodal training, were beneficial for increasing serve speed in tennis players. Further high-quality research is recommended to confirm this conclusion.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_ record.php?RecordID=519790, identifier CRD42024519790.